The Swiss cheese of trade policy: The case against product exclusions in trade agreements - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2018)
There have been calls to exclude certain products from trade agreements because they cause damages to public health or the environment. Lately, campaigns for product exclusions have included chemicals (generally or specific chemicals like glyphosate), sugary drinks and candy (or sugar generally), and alcoholic beverages. Previously the same case has been made for tobacco products. In this paper, it is argued that product exclusions are neither legally feasible nor desirable. Measures to exclude products would run foul of the rules and market-access commitments that countries have agreed in the WTO, and that serve as a basis also for other trade deals, like bilateral Free Trade Agreements. Importantly, excluding products from current market-access commitments in the WTO would per se do nothing with regard to public health because the main effect is that local production of the excluded goods would substitute goods that are now imported. The conclusion is that trade policy is not a tool for regulatory ambitions. Nor does it stand in the way for regulations that aim to improve public health. Trade policy concerns trade, and the instruments and agreements that exist for the pursuit of better and less-discriminatory trade conditions simply cannot be used for sundry regulatory proposals, however relevant they may be.
Keywords: 330